Discovery of a Novel, Selective and Irreversible Inhibitor (Abivertinib) of Mutated EGFR and T790M-induced Resistance for the Treatment of NSCLC - Long Mao; Wei Tang; Xiaoying Zhang; Jia Liu; Yile Chen; Yuning Hua; Bojie Weng; Xiaopeng Mo; Yimei Bao; Li Teng; Lijun Xu; Yuren Zhang; et al. (Elsevier, 2020)
Three chemical series of heterocyclic small molecules were designed and synthesized as the 3rd generation EGFR inhibitors. Detailed structure-activity relationship (SAR) studies and lead optimization (from 1a to 4d) were descripted. With the support of molecular modeling and evaluation through biochemical and cellular assays, liver microsomal/ plasma/ blood stability studies, preliminary rat PK screening and in vivo animal models, pyrrolopyrimidine-based compound 4d (abivertinib, AC0010), a novel potent and highly selective irreversible EGFR inhibitor, was discovered.Unlabelled ImageThis compound has been being clinically investigated in several countries including China, the United States, and Europe. Structurally distinct from those irreversible pyrimidine-based EGFR inhibitors (rociletinib, and recently approved osimertinib), abivertinib (AC0010) has demonstrated significant clinical benefit with good safety profiles (through a different metabolic pathway and possibly different resistance mechanism compared to both osimertinib and rociletinib) in NSCLC patients who had progressed on previous therapy, which provides an alternative therapeutic agent for NSCLC patients who develop acquired resistance to first generation EGFR TKIs.